26-Year perspective on stapled hemorrhoidopexy – insights into managing severe complications. Two case reports and literature review - Prokopchuk, O.; Fuchs, F.; Nedic, D.; Quaiser, D.; Novotny, H. F. G.; Friess, H.; Bachmann, J.; Spelsberg, F. (General Surgery, 2024)
Stapled Hemorrhoidopexy, first introduced by Longo in 1998, has become a widely adopted surgical method for treating hemorrhoidal disease. This innovative procedure gained popularity due to reduced postoperative pain, shorter hospital stays, and faster recovery. However, it is not without risk and is associated with rare but severe complications that can significantly affect patient outcomes. This study describes two illustrative clinical cases of such complications. The first case involves a 41‑year‑old male patient who developed a perirectal hematoma accompanied by acute abdominal bleeding caused by mesenteric vessel rupture at the rectosigmoid junction. Urgent surgical intervention and intensive postoperative care were required. The second case concerns a 49‑year‑old female patient who experienced anal stenosis and subsequent fecal incontinence, necessitating both surgical correction and prolonged rehabilitative therapy to restore bowel function and improve quality of life. These cases emphasize the critical importance of early recognition and effective management of complications associated with stapled hemorrhoidopexy. They also highlight the necessity of a multidisciplinary approach involving colorectal surgeons, general surgeons, and gastroenterologists to optimize patient care. A comprehensive literature review identifies key risk factors for complications, including patient comorbidities, technical nuances of the procedure, and the careful selection of candidates. Best practices for preventing and managing complications are also discussed, focusing on surgical technique refinement, thorough preoperative evaluation, and enhanced staff training. These insights aim to equip clinicians with essential knowledge to minimize risks, enhance patient safety, and maintain the advantages of this innovative method.